Evaluating reticulocyte hemoglobin as a marker of iron depletion in pediatric patients in Banda Aceh - Ayu Rezky Oktariany; Syafruddin Haris; Heru Noviat; Sulaiman Yusuf; Eka Destianti Edward; Rusdi Andid (AcTion: Aceh Nutrition Journal, 2026)
Anemia in children remains a major public health problem worldwide and in Indonesia, where national data report a prevalence of 21.7% among children aged ≥1 year. Iron deficiency is the leading cause, with iron depletion representing the earliest subclinical stagewhich is often difficult to detect using conventional parameters. Reticulocyte hemoglobin (Ret-He) has been proposed as a marker of functional iron availability during erythropoiesis. This study aimed to evaluate the diagnostic performance of Ret-He in identifying iron depletion in pediatric patients. A cross-sectional analytical study was conducted at Dr. Zainoel Abidin General Hospital in Banda Aceh between July and September 2024. A total of 87 pediatric patients aged 1 month to 18 years were initially enrolled; after excluding subjects with anemia to focus on the iron depletion stage, 54 children were included in the final analysis. Iron depletion was identified in 12.6% of the subjects. Receiver operating characteristic (ROC) analysis showed an optimal Ret-He cut-off value of 29.5 pg, with an area under the curve (AUC) of 0.609, sensitivity of 70%, specificity of 63.6%, and a non-significant p-value (p = 0.398), indicating a limited diagnostic accuracy. Ret-He levels were significantly positively correlated with mean corpuscular volume (MCV) (r = 0.444; p = 0.001) and mean corpuscular hemoglobin (MCH) (r = 0.511; p < 0.001), but were not significantly associated with hemoglobin, ferritin, or transferrin saturation. In conclusion, Ret-He cannot be used as a standalone diagnostic marker of iron depletion in pediatric patients. However, its association with erythrocyte indices suggests that Ret-He may serve as a complementary parameter when interpreted alongside conventional iron status markers during the early evaluation of iron-related disorders.